2010
DOI: 10.1111/j.1365-2702.2009.03090.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ experiences of their first encounter with death during clinical practice in Taiwan

Abstract: Several recommendations have been made, including teaching and support not only in the period of dying, but at the moment of patient death and postmortality. Avoiding topics about death in local culture have been noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…The major impact of the first experience of death has also been described by other authors who highlight the need for training on this issue (Huang et al . , Kent et al . , Whyte et al .…”
Section: Discussionmentioning
confidence: 99%
“…The major impact of the first experience of death has also been described by other authors who highlight the need for training on this issue (Huang et al . , Kent et al . , Whyte et al .…”
Section: Discussionmentioning
confidence: 99%
“…The reported emotional exhaustion of the students that emerged as a finding of the current study stresses the necessity of high-quality preparation and support to both professional nurses and nursing students in relation to the care of terminally ill patients [9,12,13]. The emotional depletion seemed to be experienced by the students as a situation that they could not escape from.…”
Section: Resultsmentioning
confidence: 71%
“…This aspect facilitated their clinical experiences and promoted their abilities to provide efficient care to the patients tackling difficult situations. On the contrary, in the studies of Huang et al [12] and http://Saarikoski et al [24], nursing students reported that during the period of caring for near-death patients, mentors and nurses were providing guidance and support in terms of preparing the students caring for terminally ill patients while little help was given during the dying process and the bereavement phase. The lack of support resulted in struggling to manage their feelings and ill-prepared them to offer support for the loved ones left behind.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations